Calcium influx, oxidative stress, and apoptosis induced by TRPV1 in chronic myeloid leukemia cells: Synergistic effects with imatinib - Maggi, Federica; Morelli, Maria Beatrice; Aguzzi, Cristina; Zeppa, Laura; Nabissi, Massimo; Polidori, Carlo; Santoni, Giorgio; Amantini, Consuelo (Frontiers in Molecular Biosciences, 2023)
Introduction: Calcium flux is the master second messenger that influences the proliferation-apoptosis balance. The ability of calcium flux alterations to reduce cell growth, makes ion channels interesting targets for therapy. Among all, we focused on Transient Receptor Potential Vanilloid 1 (TRPV1), a ligand-gated cation channel with selectivity for calcium. Its involvement in hematological malignancies is poorly investigated especially in the field of chronic myeloid leukemia (CML), a hematologic malignancy characterized by the accumulation of immature cells. Methods: By using FACS analysis, western blot analysis, gene silencing and cell viability assay, we investigated the activation of TRPV1, by N-oleoyl-dopamine (OLDA), in CML cell lines. Results: We demonstrated that the triggering of TRPV1 inhibits cell growth and promotes apoptosis of CML cells. Its activation induced calcium influx, oxidative stress, ER stress, mitochondria dysfunction and caspase activation. Interestingly, a synergistic effect by OLDA and the standard drug imatinib was found. Conclusion: Overall, our results support that TRPV1 activation could be a promising strategy to enhance conventional therapy and improve management of CML.